MOTIVASI DAN TINGKAT KETEPATAN FOREHAND DRIVE PADA PESERTA DIDIK EKSTRAKURIKULER TENIS MEJA MTSN 6 BANJAR - Wardi, Sahra; Abdul Hamid; Ramadhan Arifin (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2024)
This research aims to determine the motivation and level of accuracy of the forehand drive in the MTsN 6 Banjar table tennis extracurricular. The method used was quantitative descriptive with a porposive sampling technique with a sample of 16 students out of 20 students. The instruments used are in the form of a questionnaire and a test of the level of forehand drive accuracy. From the results of the questionnaire, it can be seen that students have motivation in the good category 45% of the 236 answers, the very good category 40% of the 212 answers, the medium category 14% of the 14% answers, the poor category 1% of the 6 answers. Meanwhile, the level of forehand drive accuracy from the 16 samples was 6.3% or 1 participant was in the good category, 12.5% or 2 participants were in the sufficient category, 18.8% or 3 participants were in the poor category, 62.5% or 10 participants were in the good category. very poor category. The difficulty experienced by students is that when making a shot, students are not calm when the ball hits the bet, so that the ball still goes out of court, hits the net, and the ball bounces too high on the table. When practicing precise forehand drive shots, it is hoped that students will hit the ball in places that are difficult for the opponent to reach, where when performing accurate forehand drive shots it will indirectly make things difficult for the opponent.